The exotropia food safety cultural conundrum: A case study of a UK fish high-risk processing company. (January 2022) - Watson, Derek; Nyarugwe, Shingai P.; Hogg, Robert; Griffith, Chris; Luning, Pieternel A.; Pandi, Sophia
Abstract: Food safety continues to be a challenge worldwide despite scientific advances, continuous improvement in food safety management systems and increasing academic debate on food safety. This paper aims to validate a new model of food safety cultural compliance to identify the challenges that organisations face in their pursuit of a positive food safety culture. A mixed-method approach was adopted via the quantitative analysis of a stage one 'Enlighten Questionnaire' involving 202 respondents using parametric statistics (ANOVA with appropriate Post-Hoc tests and t-tests). Hochberg's GT2 was used for the Post-Hoc tests due to different group sizes and appropriate non-parametric tests were also run to confirm these results. Qualitative analysis of stage two semi-structured interviews totalling 40 participants and stage three focus groups each consisting of 3 groups of 9 employees equating to 27 participants was utilised. Thematic analysis was adopted to synthesise and cluster key themes. Our findings identify the misalignment of management and employees in the pursuit of establishing and embedding a positive food safety culture. Four key themes of the Enlighten Food Safety Culture Model (EFSCM) namely; Control, Co-operation, Communication and Competence were core cultural factors that could be used to realign management and employee behaviours to help stimulate a positive food safety culture. Highlights: Quality assurance systems do not guarantee food safety compliance. Food Safety Culture relies on both management and employee commitment. Control, Co-operation, Communication and Competence are food safety benchmarks.